INNOVATIVE CAPACITY OF REGIONAL ECONOMIC SYSTEMS IN THE CONDITIONS OF FORMATION OF CREATIVE ECONOMY: CURRENT CHALLENGES FOR UKRAINE - KHANIN, Semen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the innovative capacity of regional economic systems in the context of the formation of a creative economy. It is substantiated that the post-industrial progress of social development in the direction of the formation of a creative economy makes it possible to increase the competitiveness of regional economic systems at the national and international levels. It is found that the creative economy is a modern model of the economy based on the use of creative ideas, innovations, cultural potential and intellectual resources as key factors of production and socio-economic development. The creative economy is focused on the creation of intangible values, such as knowledge, art, technology, design and other creative products that have economic and social value. The need for institutional support for the formation of a creative economy for the development of creative industries, which include socio-cultural aspects, such as support for art, design, architecture, cinematography, etc. is determined. The importance of forming intellectual and human resources, which must have the appropriate skills and competencies that are currently in demand for skilled labor, is proven. Taking into account the fact that for the formation of a creative economy and support for the competitiveness of economic entities through the implementation of new ideas, the innovative capacity of the country’s regional economic systems is of great importance, an analysis of the country’s rating according to the Global Innovation Index for 2019-2024 was conducted. A study of the dynamics of changes in Ukraine’s rating according to the Global Innovation Index made it possible to outline the main reasons for the decline in its indicators and identify directions for leveling the negative trend of the index decline. The main determinants of the intellectual and innovative development of regions have been formed, which, with their effective development, allow for the rapid restoration of the potential of regional economic systems on the principles of intellectual and innovative development. The development of regional economic systems in the context of a creative economy requires an integrated approach based on human capital, innovation, support for entrepreneurship and the integration of traditional and new industries.